Pengaruh Perendaman Zat Pengatur Tumbuh Giberelin (GA3) pada Perkecambahan Benih Kopi Arabika (Coffea arabica L.) Varietas S795 - Rohman, Febri Ainur; Taufika, Ramadhan (Politeknik Negeri Lampung, 2024)
Coffee is one of the plantation commodities that has an important role in the national economy, especially as a source of foreign exchange because it has high economic value. The productivity of arabica coffee (Coffea arabica L.) in Indonesia in the 2019/2020 period decreased by 2.7% with a total production of around 95 million sacks. This study aims to determine the effect of gibberellin (GA3) on the germination of the arabica coffee bean variety S795. The experimental design was a completely randomized design factorial consisting of two factors with four replications for each treatment. The first factor was the plant growth regulator gibberellin concentration which consisted of 100 ppm (K1), 200 ppm (K2), and 300 ppm (K3). The second factor is the soaking time which consists of 12 hours (P1) and 24 hours (P2). The result showed that the interaction between GA3 concentration and soaking time had no significant effect on all observed parameters (germination percentage, germination rate, seedling height) in the germination of arabica coffee bean variety S795. Based on the table of average interactions between GA3 concentration and soaking time, it can be concluded that the K1P1 treatment with 12 hours of soaking time at a concentration of 100 ppm was the best treatment for the parameters of germination percentage, seedling height, and root length. The K2P1 treatment with 12 hours of immersion time at a concentration of 200 ppm was the best treatment for the germination rate parameter, namely 36.34 days.